Second screen and Political Talk-Shows: Measuring and Understanding the Italian Participatory Couch Potato - Giglietto, Fabio (AoIR Selected Papers of Internet Research, 2013)
According to several recent reports, the practice of using a ‘second screen’ while following a television program is quickly becoming a widespread phenomenon. When the secondary device is used to read or contribute to online comments about a watched program, most of the discussion takes place on popular social media such as Facebook and Twitter. The paper presents what is, to our knowledge, the first study on a full season dataset of Twitter conversations about a TV genre. Starting from August 2012, we collected all the Tweets (1,703,064) containing at least one of the official hashtags of the eleven political talk shows (607 episodes) aired by the Italian free-to-air broadcasters. We found a significant correlation between the Tweet-rate-per-minute during airtime and the audience of the show’s episode. Furthermore, we demonstrate a technique, based on cluster analysis, aimed at identify key moment in a season. On this subset of contents, we applied qualitative content analysis to identify users’ level of participation on the scale of access, interaction and participation.